Targeted antifungal delivery system: beta-glucosidase sensitive nystatin-star poly(ethylene glycol) conjugate - Bílková, Eliška; Imramovský, Aleš; Buchta, Vladimír; Sedlák, Miloš (International journal of pharmaceutics, 2010)
A new targeted intravenous conjugate of nystatin with pentaerythritol poly(ethylene glycol)ether has been prepared and characterised (NY(4)-sPEG, M=25 160). The conjugate contains a beta-d-glucopyranoside molecular switch sensitive to beta-glucosidases (E.C.3.2.1.21), which are specifically present in the enzyme outfit of fungal pathogens. The investigated conjugate is stable under in vitro conditions for 24h (solution of phosphate buffer pH=7.4). Spectrophotometrically controlled releasing of nystatin in model medium containing beta-glucosidase ((Aspergillus niger) 2mg/mL, 66.6 units/g; pH 7.4, 2 x 10(-2)M), reported decomposition half-life of conjugate tau(1/2)=(88+/-2)s. This implies that releasing of nystatin is controlled only enzymatically.
Keywords: farmaceutická chemie; stabilita léku; Antifungal Agents; Kinetics; Half-Life; Propylene Glycols; hydrolýza; Hydrogen-Ion Concentration; celulasy; Nystatin; Polyethylene Glycols; vysokoúčinná kapalinová chromatografie; Drug Carriers; Chemistry, Pharmaceutical; Chromatography, Gel; Buffers; spektrofotometrie ultrafialová; Solubility; Drug Stability; rozpustnost; poločas; Cellulases; farmaceutická technologie; příprava léků; polyethylenglykoly; magnetická rezonanční spektroskopie; propylenglykoly; Chromatography, High Pressure Liquid; léky s prodlouženým účinkem; Delayed-Action Preparations; nystatin; Aspergillus niger; Hydrolysis; Spectrophotometry, Ultraviolet; nosiče léků; gelová chromatografie; Drug Compounding; Magnetic Resonance Spectroscopy; pufry; antifungální látky; koncentrace vodíkových iontů; kinetika; Technology, Pharmaceutical